Is Fluorescence Under an Alternate Light Source Sufficient to Accurately Diagnose Subclinical Bruising?. Issue 2 (12th February 2015) - Lombardi, Maria; Canter, Jennifer; Patrick, Patricia A.; Altman, Robin
Abstract This single‐blinded, randomized validation study was conducted to evaluate whether fluorescence under alternate light sources (ALS) is sufficient to diagnose subclinical bruising (bruising not visible under white light). Standardized trauma was induced on randomly selected ventral forearms. On days 1, 7, and 14 investigators independently examined case forearms under white light for perceived bruising and under ALS for fluorescence and compared body maps. 56 case and 62 control forearms (n = 118) were examined. Sensitivity of ALS on days 1, 7, and 14 was 76.8%, 69.6%, and 60.7%, respectively, compared to 69.6%, 60.0%, and 32.1% for white light. The specificity of ALS on days 1, 7, and 14 was 51.6%, 59.7%, and 53.2%, respectively, compared to 71.0%, 81.4%, and 86.9% for white light. ALS has increased sensitivity yet low specificity compared to white light in accurately detecting bruises. Fluorescence under ALS is not sufficient to accurately or responsibly diagnose subclinical bruising.